Meckel Gruber Syndrome: Correlation Between Prenatal Diagnosis and Autopsy Findings - Hülya Akgün; Mahmut Tuncay Özgün; Arzu Taşdemir; Arzu Aydın; Çağdaş Türkyılmaz; Mustafa Başbuğ (Medical Network, 2008)
OBJECTIVE: To analyze prenatal sonographic anomalies detected in fetuses with Meckel Gruber syndrome (MGS), and to correlate these anomalies with autopsy findings. STUDY DESIGN: In a 4-year long prospective study, ultrasound findings were compared with fetal autopsy findings in eight fetuses with MGS out of 107 second-trimester termination of pregnancy (TOP) cases due to fetal malformation diagnosed by second trimester-ultrasound examination at a tertiary referral center. RESULTS: Eight prenatally diagnosed fetuses with MGS were analyzed. Seven cases had classical clinic triad. One case had only polycystic kidneys and polydactyly. Fetal autopsy confirmed all prenatally diagnosed findings associated with MGS; fetal examination added polydactyly in two prenatally undiagnosed cases. Hepatic lesions were found in four cases which were determined during the histologic examination. CONCLUSION: Ultrasonographic findings of MGS allow for diagnosis of the most cases. However autopsy may be valuable for confirmation of the diagnosis and to evaluate the recurrence risk in future pregnancies.